2012
DOI: 10.1590/s1516-35982012000300034
|View full text |Cite
|
Sign up to set email alerts
|

Intake, digestibility, rumen characteristics and microbial protein synthesis efficiency in bovine and bubaline fed sugar cane silage with additives

Abstract: -Intake and total and ruminal digestibility, ruminal characteristics and microbial synthesis efficiency in bovine and bubaline fed sugar cane silages treated with microbial additive Lactobacillus buchneri (inoculate) and the addition of: cassava byproduct meal at 250 g/kg; soybean hulls at 250 g/kg; and urea at 33 g/kg, in natural matter were evaluated. The forage:concentrate ratio was 600:400 g/kg. Bubaline body weight (BW) was 403±49 kg and bovine BW was 492±10 kg. The experimental design consisted of two 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
4
0
4
Order By: Relevance
“…In this study, an increase in the intake of NPN, derived from urea, probably resulted in a higher concentration of rumen NH 3 -N (24.5 mg/dL), as found by [ 34 ]. The maximum rumen NH 3 -N presented is accordance with the amount (10 to 23 mg/dL) suggested by [ 35 ] for maximum for maximum rumen fermentation activity and microbial growth.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, an increase in the intake of NPN, derived from urea, probably resulted in a higher concentration of rumen NH 3 -N (24.5 mg/dL), as found by [ 34 ]. The maximum rumen NH 3 -N presented is accordance with the amount (10 to 23 mg/dL) suggested by [ 35 ] for maximum for maximum rumen fermentation activity and microbial growth.…”
Section: Discussionsupporting
confidence: 89%
“…() reported that ruminal bacteria obtained from 630 to 800 g/kg of their N requirements from the ruminal NH 3 ‐N pool and thus the remaining 200 to 370 g/kg of their N requirements from non‐NH 3 ‐N (NAN), primarily in the form of amino acid and peptides. However, the total amount of microbial protein flowing to the small intestine depends on nutrient availability and efficiency of use of these nutrients by the ruminal bacteria (Cutrignelli et al., ; Calabrò et al., ; Maeda et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Sugar cane silage with maniçoba positively influences the performance of animals fed with this silage compared to the control. In evaluating the digestibility of sugar cane silage with Lactobacillus, urea, and agricultural by-products, a higher rate of degradation of the b fraction (0.027% h -1 ) was found (Maeda et al, 2011), as well as higher consumption (7.54 kg DM d -1 ) in cattle fed with sugar cane silage with inoculants (Maeda et al, 2012).…”
Section: Variablesmentioning
confidence: 98%